2018
DOI: 10.1007/s13193-018-0786-y
|View full text |Cite
|
Sign up to set email alerts
|

Occult Gallbladder Carcinoma Presenting as a Primary Ovarian Tumour: a Case Report and Review of Literature

Abstract: The ovary is a common site of metastasis from various organs. However, little is known about gallbladder carcinoma metastasising to the ovaries and presenting as a primary ovarian tumour. We report a case of a metastatic gallbladder carcinoma which mimicked a primary ovarian tumour in a 31-year-old woman who presented with menstrual symptoms and an ovarian mass without obvious signs and symptoms related to gallbladder carcinoma. Postoperatively histopathological examination diagnosed primary ovarian germ cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(43 reference statements)
0
6
0
1
Order By: Relevance
“…GC is a severe malignancy. Based on statistical data, the 5-year survival of cases with GC is lower than 10%, and such a high mortality is one the problems needed to be solved urgently for clinicians [ 15 ]. We believe that such a high mortality is due to the following reasons: Firstly, GC is insidious at the onset, and it has no evident clinical features in the early phase, so it is prone to be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…GC is a severe malignancy. Based on statistical data, the 5-year survival of cases with GC is lower than 10%, and such a high mortality is one the problems needed to be solved urgently for clinicians [ 15 ]. We believe that such a high mortality is due to the following reasons: Firstly, GC is insidious at the onset, and it has no evident clinical features in the early phase, so it is prone to be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Dentro de las formas más raras de diseminación se ha reportado metástasis de este cáncer a endometrio, ovario, mama, cérvix y periumbilical. [11][12][13][14][15] El epónimo de "Ganglio de Virchow", y "Ganglio de Troisier" u otras veces llamado también "Ganglio de Virchow-Troisier", refiere al compromiso metastásico de los ganglios supraclaviculares izquierdos secundario a carcinoma avanzados, siendo el estómago como lesión primaria más frecuente. 16 Pero, también lo podemos encontrar en malignidades de tórax, abdomen y pelvis ya que el lugar de aparición de esta lesión tiene relación con la desembocadura del conducto torácico en la vena subclavia izquierda, donde se drena la linfa de estas regiones a la circulación sistémica.…”
Section: Discussionunclassified
“…In a retrospective study over 147 patients, Li W et al [14] reported a rate of ovarian metastases of 48.9% by colorectal cancer, 40.8% by gastric cancer, 8.2 by breast cancer and only 1.4% by biliary origin. Unfortunately, there are very few reports that describe cases of metastatic lesions that present clinically as a primary tumor [7,8,[15], [16], [17]]. The high rate of bilaterality, surface involvement by tumor cells, multinodular growth, extensive extra-ovarian tumor, size >10 cm, infiltrative and nodular pattern of invasion, and presence of signet ring cells are the most helpful features for indicating a metastatic nature of an ovarian mass [7,[18], [19], [20], [21]].…”
Section: Discussionmentioning
confidence: 99%
“…This cancer commonly spreads by direct extension to the liver and adjacent organs of the gastrointestinal tract. Gallbladder cancer with ovary spread is quite rare with only few reports available in the English literature [[4], [5], [6], [7], [8]].…”
Section: Introductionmentioning
confidence: 99%